Fractality of concentric structures in space of ecologic-urban planning systems - Ustinova, Iryna (КНУБА, 2017)
Conditions and stages of formation of the fractally embedded set of concentric zones of accessibility of cities on the example of Kiev are considered. The number of “levels of embedding” of such a set depends on the attractiveness and status of the city. It was established that discontinuity of space developing is associated with economic develop ment and engineering and transport networks. A rapid growth of these networks leads to the transformation of the traditionally central type of irregularity of developing the space into the multinuclear clustered systems of settlement. In the zone of Kiev influence, there are five qualitatively differed by intensity of socioeconomic links and speed of movement belts are distinguished. On the base of quantitative characteristics of these belts, it was established that in successive transition of developmental processes from local to regional and interregional levels of integrity of the ecologic-urban planning system − “population↔environment”, the expansion of its spatial boundaries and peculiar “compression” of temporary ones occur that is manifested by intermittent increase in the radius of city’s influence area – the center of system of settlement expressed in kilometers. For analysis of processes of multi-level development of ecologic-urban planning systems, the dynamics of indices of development is not as much important as characteristics of their accelerations.
Keywords: sustainable development; fractality; spatial structures; ecologic-urban planning systems; areas of cities influence.; 711.4:504